Performance Analysis of Proxmox and Virtualbox with Overhead and Linearity Parameters to Support Server Administration Practice - Aam Kholid Alfaif; Puspanda Hatta; Endar Suprih Wihidayat (Journal of Informatics and Vocational Education, 2024)
In the informatics and computer engineering education study program, there is a computer network administration course. One of the competencies in that course is server administration. Server administration practices require virtual servers that have good performance to support server administration practices. The previous students used VirtualBox in server administration practice. The use of VirtualBox is felt to be lacking in terms of performance. Therefore, it takes a virtual server that has better performance than VirtualBox. Researchers used a Proxmox virtual server to compare its performance with VirtualBox. The performance test uses overhead and linearity parameters. The results showed that when testing the performance of overhead and linearity parameters, proxmox was able to run ten virtual machines according to the research scenario. While in VirtualBox, you are only able to run three virtual machines. The overhead on proxmox is 8.3 to 15.1 seconds. While the overhead on virtualbox is higher than that on proxmox, which is 84.2 to 155.8 seconds, The graph of overhead values on Proxmox is also more stable and constant than that on VirtualBox. As for the linearity on proxmox, the value is 85.3 to 858.64 seconds. While the linearity in VirtualBox is 241.07 to 2247.15 seconds, The graph of linearity values on Proxmox also experienced a more stable increase than VirtualBox. The conclusion of this research is that the performance of proxmox with parameters for overhead and linearity is better than that of virtualbox in supporting server administration practices.